Design of a new solar dryer system with swirling flow for drying seeded grape - Cakmak, Guelsah; Yildiz, Cengiz (Pergamon-Elsevier Science Ltd, 2009)
In this study solar energy supported, swirling flow new drying system is designed and artificial drying of grapes grown around Elazig/Turkey is investigated. With the developed swirling flow dryer with airy solar collector it is examined that drying occurs homogenously and lower moisture values are obtained in when compared with classical drying system. Also it is found that with an increase in the drying air velocity decreases drying time. When air directing elements are placed inside drying chamber and rotating element to the entrance, it is examined that drying time gets shorter compared to that of natural drying. Thus, drying time which is 200 h in natural conditions decrease to 80 h with an air velocity of 1.5 m/s with the developed solar energy supported swirling flow dryer. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Drying; Seeded grape